Influence of growth parameters on the morphology of GaAs nanowires grown on Si (111) by molecular beam epitaxy. (1st June 2020) - Arpapay, Burcu; Duygulu, Özgür; Serincan, Uğur
Abstract: We report on the impact of Ga and As flux on GaAs nanowires (NWs) morphology grown by Ga assisted molecular beam epitaxy on epi-ready Si (111) substrates. The results are presented in terms of growth rate, density and diameter of NWs. It is demonstrated that an increase in the As flux by a factor of 4 results in an increase in the growth rate of GaAs NWs by a factor of 3.4. It is perceived that while the average diameter of the GaAs NWs is more sensitive to the increase in the Ga flux, the amount of As flux is important for having longer NWs with a tapering around 1.0%. However, a tapering around -1.4% in GaAs NWs is obtained under high As/Ga flux ratio of 80. Besides, it is revealed that relatively high As/Ga flux ratio consumes the Ga droplets at the tip of the GaAs NWs which results in the change of NW diameter. Above all, it is shown that a change in growth mechanism from vapor-liquid-solid to vapor-solid occurs in the case of high As/Ga ratio which appears at the bottom region of GaAs NWs.